Supporting Nepal’s Federal Transition through research and engagement on the devolution of the agricultural sector. - CGIAR Research Program on Policies, Institutions, and Markets (2017)
A study demanded by Nepal’s Ministry of Agricultural Development (MoAD) analysed how agriculture has been devolved in other federal or quasi-federal settings and generated primary data on the concerns of district-level agricultural service providers and rural households in Nepal. Through repeated engagement with high-level policymakers, MoAD adopted suggestions in the study on food technology and quality control and the structure of agricultural training centers. Moreover, MoAD accepted Kenya as a model for devolution and undertook a study tour there.